Malignant melanoma among lithographers - Nielsen, H.; Henriksen, L.; Olsen, Jørgen H. (Scandinavian Journal of Work, Environment & Health, 1996)
' ' OBJECTIVES ': 'Mortality studies have suggested that workers in the printing industry may have a higher incidence of malignant melanoma. The aim of this study was to assess the incidence of malignant melanoma among lithographers.' ' METHODS ': 'A cohort of 837 lithographers, born in 1933–1942, was followed in the Danish Cancer Register from 1974 to 1989.' ' RESULTS ': 'Five cases of malignant melanoma were found, with 1.5 expected (relative risk 3.4, 95% confidence interval 1.2–7.5).' ' CONCLUSION ': 'Many known and suspected carcinogens are used in the printing industry. Hydroquinone, used for photographic development, may be implicated in the observed increase in risk, as it causes depigmentation and changes in melanocytes in the skin.
Keywords: cancer risk; hydroquinone